Sustainable Urbanism Revisited: A Holistic Framework Based on Tradition and Contemporary Orientations - Oktay, Derya (Igi Global, 2012)
At a time of uncontrolled globalization in which serious environmental problems are threatening cities and their inhabitants, as cultural integrity is constantly under attack and many cities lack socially inclusive and responsive environments, there is an urgent need for a radical shift towards a holistic strategy for sustainable urbanism combining ecological sustainability and socio-cultural sustainability. This calls for sensitivity to the traditional urbanism and impact of global ideas, practices, and technologies on local social and cultural practices. In line with these, this chapter aims to establish an environmentally sound and human friendly framework for sustainable urbanism. In this context, the study firstly provides a conceptual understanding of sustainable urbanism and a critical review of its philosophical and practical framework; secondly, it provides an assessment of contemporary approaches to sustainable urbanism; thirdly, the chapter analyses the traditional Turkish (Ottoman) city which provides valuable clues for sustainable development, and discusses possible research directions that could help promote the concept of sustainable urbanism.
Keywords: Sense; Community; Design